Comparison of cell death-inducing effect of novel taxane SB-T-1216 and paclitaxel in breast cancer cells - Kovár, Jan; Ehrlichová, Marie; Smejkalová, Barbora; Zanardi, Ilaria; Ojima, Iwao; Gut, Ivan (Anticancer research, 2009)
BACKGROUND: In this study, the effect of novel taxane SB-T-1216 and paclitaxel on sensitive MDA-MB-435 and resistant NCI/ADR-RES human breast cancer cells was compared. MATERIALS AND METHODS: Cell growth and survival were evaluated after 96-hour incubation with tested concentrations of taxanes. The effect on the formation of microtubule bundles was assessed employing fluorescence microscopy and on the cell cycle employing flow cytometric analysis. The activity of caspases was assessed employing commercial colorimetric kits. RESULTS: The IC(50) (concentration resulting in 50% of living cells in comparison with the control) of SB-T-1216 in sensitive cells was 0.6 nM versus 1 nM for paclitaxel. However, the IC(50) of SB-T-1216 in resistant cells was 1.8 nM versus 300 nM for paclitaxel. Both SB-T-1216 and paclitaxel at death-inducing concentrations induced the formation of microtubule bundles in sensitive as well as resistant cells. Cell death induced in sensitive and resistant cells by paclitaxel was associated with the accumulation of cells in the G(2)/M phase. On the contrary, cell death induced by SB-T-1216 took place without the accumulation of cells in the G(2)/M phase but with a decreased number of G(1) cells and the accumulation of hypodiploid cells. Both SB-T-1216 and paclitaxel activated caspase-3, caspase-9, caspase-2 and caspase-8 in sensitive as well as resistant cells. CONCLUSION: Cell death induced by both paclitaxel and novel taxane SB-T-1216 in breast cancer cells is associated with caspase activation and with the formation of interphase microtubule bundles. Novel taxane SB-T-1216, but not paclitaxel, seems to be capable of inducing cell death without the accumulation of cells in the G(2)/M phase.
Keywords: doxorubicin; G2 fáze; Caspase 3; Antineoplastic Agents, Phytogenic; protinádorová antibiotika; Caspase 8; kaspasa 3; Cell Line, Tumor; G2 Phase; Cell Proliferation; Caspase 2; fluorescenční mikroskopie; G1 fáze; Taxoids; kaspasa 9; chemorezistence; nádory prsu; paclitaxel; buněčné dělení; Paclitaxel; Microtubules; kaspasa 2; lidé; Cell Division; Caspase 9; Microscopy, Fluorescence; taxoidy; Breast Neoplasms; Humans; mikrotubuly; Antibiotics, Antineoplastic; G1 Phase; apoptóza; proliferace buněk; Drug Resistance, Neoplasm; kaspasa 8; nádorové buněčné linie; fytogenní protinádorové látky; Doxorubicin; Apoptosis